PENGEMBANGAN MEDIA INTERAKTIF PADA MATERI ORGANISASI KEHIDUPAN UNTUK SEKOLAH MENENGAH PERTAMA (SMP) - Ramanda, Welia; Megahati S, RRP; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The use of media in teaching and learning can clarify students understanding of the subject matter and can make the learning process more interesting and effective . But the reality in the learning process , teachers are not using the medium of learning because teachers are not able to make instructional media and just rely on the book as a source of learning , thus making the students find it difficult to understand the material . Associated with it is developed interactive media on the material organization of life for SMP . This study aims to produce an interactive media organizations on the material of valid and practical life . This type of research is the development of research by using a 4 - D models which consists of 4 stages , namely , the definition (define) , design (design) , development (develop) and the spread (disseminate) , but the deployment phase (disseminate) is not done . Define phase consists of a curriculum analysis , analysis of students and media analysis . At the design stage to design interactive media . At this stage of develop test the validity and practicalities . Test validity by a validator which consists of 2 lecture of biology and 1 junior high school biology teacher . Test practicalities by 1 biology teacher and junior class VII Perti Padang . These data were analyzed with descriptive analysis . The results of the validity test of interactive media by validator shows that interactive media is in the valid criteria ie 86.25 % in terms of variable material / content, form of media , motivation , and language . Test results practicalities of interactive media by teachers indicate that interactive media is in a very practical criterion is 88.67 % and the test results demonstrate the practicalities of interactive media by students is located in a very practical criterion is 86.72 % in terms of practicality variable ease of use , availability time , the appeal of the device , interpreted the material , which is the same as the equivalent of teaching materials and evaluation. This suggests that interactive media on the material life of the resulting organization is valid and very practical .Â